THE EFFECT OF WORKLOAD ON EMPLOYEE PERFORMANCE WITH WORK SPIRIT AS AN INTERVENING VARIABLE AT PT. PERKASA MITRA PERKASA HIGH CLICK - Rusmewahni, Rusmewahni; Meilisa, Ingka (International Conference on Health Science, Green Economics, Educational Review and Technology, 2021)
Good performance will encourage the company to achieve its goals, while poor performance will hinder every company process to achieve company goals. PT. Perfect Mitra Perkasa Tebing Tinggi is a company engaged in the pharmaceutical sector which is a distributor of drugs. For North Sumatra, Aceh and Riau. At PT. Perfect Mitra Perkasa Tebing Tinggi performance phenomenon in the warehouse division that can be seen and felt is slow performance. The following conclusions can be drawn: The first hypothesis is accepted, meaning that workload (X) affects morale (Z), The second hypothesis is accepted, meaning that workload (X) affects employee performance (Y), The third hypothesis is accepted, meaning that employee performance (Y) affects morale (Z), The fourth hypothesis is accepted, meaning that workload (X) affects employee performance (Y) with morale (Z) as the intervening variable